THE ROLE OF DIGITAL MARKETING, E-WOM, AND FOMO ON CONSUMER PURCHASE DECISIONS ATSEDUH RASA COFFEE SHOP - M. Akbar Anugrah; Pandi Putra; Andi Alfianto Anugrah Ilahi; Bakhtiar Tijjang; Safrida (Journal of Social and Economics Research, 2026)
This study aims to: (1) analyze the influence of Digital Marketing on purchasing decisions at Seduh Rasa Coffee Shop; (2) analyze the influence of Electronic Word of Mouth (E-WOM) on purchasing decisions at Seduh Rasa Coffee Shop; and (3) analyze the influence of Fear of Missing Out (FOMO) on purchasing decisions at Seduh Rasa Coffee Shop. The development of digital technology and social media has driven changes in consumer behavior regarding how they obtain information, provide reviews, and make purchasing decisions. Therefore, Digital Marketing, E-WOM, and FOMO are factors that need to be considered to enhance consumer purchasing decisions within the coffee shop industry. This study employs a quantitative approach using a survey method. The population consists of all consumers of Seduh Rasa Coffee Shop. A sample of 80 respondents was selected based on Roscoe's approach, utilizing the incidental sampling technique. Data collection was conducted via questionnaires, followed by analysis using the multiple linear regression method. The results indicate that, individually, Digital Marketing does not have a significant effect on consumer purchasing decisions. Electronic Word of Mouth (E-WOM) also does not have a significant effect on purchasing decisions. Meanwhile, Fear of Missing Out (FOMO) has a positive and significant effect on purchasing decisions. Simultaneously, Digital Marketing, Electronic Word of Mouth (E-WOM), and Fear of Missing Out (FOMO) have a positive and significant effect on purchasing decisions, with an F-calculated value of 86.267, which exceeds the F-table value of 2.72. The coefficient of determination (R²) value of 0.782 indicates that 78.2% of the variation in purchasing decisions can be explained by these three independent variables, while the remaining 21.8% is explained by other variables not examined in this study. The implications of this research suggest that the management of Seduh Rasa Coffee Shop needs to optimize marketing strategies capable of creating consumer appeal and a sense of urgency, thereby increasing purchasing decisions.